2000
DOI: 10.1128/jb.182.14.4124-4127.2000
|View full text |Cite
|
Sign up to set email alerts
|

All Major Regions of FtsK Are Required for Resolution of Chromosome Dimers

Abstract: Resolution of chromosome dimers, by site-specific recombination between dif sites, is carried out in Escherichia coli by XerCD recombinase in association with the FtsK protein. We show here that a variety of altered FtsK polypeptides, consisting of the N-terminal (cell division) domain alone or with deletions in the prolineglutamine-rich part of the protein, or polypeptides consisting of the C-terminal domain alone are all unable to carry out dif recombination. Alteration of the putative nucleotide-binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…least one other protein, FtsK, is required for resolution of chromosome multimers in vivo (10,37). B. subtilis SpoIIIE and YtpT are, respectively, 48 and 49% identical to the C terminus of the E. coli FtsK protein.…”
Section: Deletion Induced Filamentationmentioning
confidence: 99%
“…least one other protein, FtsK, is required for resolution of chromosome multimers in vivo (10,37). B. subtilis SpoIIIE and YtpT are, respectively, 48 and 49% identical to the C terminus of the E. coli FtsK protein.…”
Section: Deletion Induced Filamentationmentioning
confidence: 99%
“…Finally, the putative nucleotide binding site of FtsK was critical for its role in Xer recombination. It had been previously reported that two FtsK N-terminal truncations (starting at residue 825 and 863) fused to a polyhistidine tag (Boyle et al 2000), and a protein containing domain 2 and 3 of FtsK did not complement Xer recombination at dif. However, we believe that these negative results may reflect a problem of expression or a lack of activity of the tagged proteins.…”
Section: The C-terminal Domain Of Ftsk Is Sufficient To Support a Commentioning
confidence: 99%
“…The 11-bp insertion is located in the second open reading frame (ORF) and contains an in-frame stop codon. The fourth ORF of this cluster encodes a protein with FtsK motifs that may be involved in cell division (2,3,4). The fifth ORF of this operon has already been identified as a M. avium subsp.…”
mentioning
confidence: 99%